Black frontiersman the memoirs of Henry O. Flipper, first Black graduate of West Point - Flipper, Henry Ossian (Texas Christian Univ. Press, 1997)
Flipper was the first black graduate from West Point and served in the Tenth Cavalry in Texas and Oklahoma before being dishonarbly discharged in 1882. He went on to be a mining engineer, surveyor, congressional aide, translator, and writer.
Keywords: Flipper, Henry Ossian <1856-1940>; Cavalerie; Frontier; Schwarze. USA; African American military cadets -- New York (State) -- West Point -- Biography; African American pioneers -- Southwest, New -- Biography; African American soldiers -- Southwest, New -- Biography; African Americans -- Southwest, New -- Biography; Frontier and pioneer life -- Southwest, New; Military cadets -- United States -- Biography; Pioneers -- Southwest, New -- Biography; USA; Southwest, New -- Race relations; Biografie